2022
DOI: 10.3389/fnut.2022.1026890
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated curcumin from Curcuma longa modulates diet-induced hypercholesterolemia in Sprague Dawley rats

Abstract: Hypercholesterolemia is one of the major causes of cardiovascular ailments. The study has been conducted on the hypothesis that hypercholesterolemia can be modulated by microencapsulated curcumin due to its enhanced bioavailability. In this context, curcumin obtained from fresh rhizomes of Curcuma longa by conventional (CSE) and supercritical fluid (SFE) extractions, has been successfully microencapsulated using a mixture of gelatin and maltodextrin. The microencapsulated curcumin CSE&SFE, has been add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Basically, two reaction processes are involved by virtue of that the citrus peel bioactive ingredient in the resultant extract triggers a protection mechanism against oxidation [134]. First, the single electron transfer method depends on the reduction of oxidation compounds like carbonyls, metals, and radicals [135].…”
Section: In Vitro Antioxidant Potentialmentioning
confidence: 99%
“…Basically, two reaction processes are involved by virtue of that the citrus peel bioactive ingredient in the resultant extract triggers a protection mechanism against oxidation [134]. First, the single electron transfer method depends on the reduction of oxidation compounds like carbonyls, metals, and radicals [135].…”
Section: In Vitro Antioxidant Potentialmentioning
confidence: 99%
“…Curcumin has been reported to have many health and therapeutic properties, and previous evidence has shown that it has strong anti-inflammatory and antioxidant properties (Uchio et al, 2021;Peng et al, 2021;Fuloria et al, 2022). Different animal studies have established curcumin's antiatherosclerotic effect, its effect in alleviating hyperlipidemia (Panahi, Ahmadi, Teymouri, Johnston, & Sahebkar, 2018;Ashraf et al, 2022), and on the expression of CAMs levels (Um et al, 2014;Pradana et al, 2019). These studies relied on different delivery curcumin formulations including solid dispersions, complexation with cyclodextrins, co-administration with piperine, as nano-particles/emulsions, and as microencapsulation/emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the encapsulation of curcumin using carboxymethylcellulose and maltodextrin has been reported [13][14][15][16][17]. It was reported that curcumin encapsulation on carboxymethyl cellulosemontmorillonite clay nanocomposite could enhance the stability and solubility of curcumin in water [18].…”
Section: ■ Introductionmentioning
confidence: 99%